1996
DOI: 10.1021/ma951444w
|View full text |Cite
|
Sign up to set email alerts
|

Stable Free Radicals Produced in Acrylate and Methacrylate Free Radical Polymerization:  Comparative EPR Studies of Structure and the Effects of Cross-Linking

Abstract: Electron paramagnetic resonance (EPR) examinations of the stable free radicals from the polymerizations of a series of monofunctional, difunctional, and trifunctional acrylates and methacrylates have been made. The continuous-wave (CW) EPR of polymers from selectively deuterated monofunctional monomers and the pulsed EPR of the nondeuterated polymers were also examined. The aim of the experiments was to attempt to clarify several points of disagreement concerning the identity and assignment of polymer free rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…[5] The hyperfine coupling constant evaluated from the line spacing (27 G) in Figure 2 is in good agreement with the literature value of 27.5 G. [29] This suggests that MCRs formed by intermolecular hydrogen abstraction also exhibit three-line EPR spectra. [28,30] The EPR spectrum observed at 27% conversion during the tBA polymerization at 60 8C is in agreement with the simulated spectrum as shown in Figure 3a and b: a a ¼ 18.1 G and a b ¼ 10.3 and 28.3 G for PRR (95%) and a b ¼ 28.0 G for MCR (5%). The small radical expelled from 1 was not detected.…”
Section: Observation Of Radicals By Epr Spectroscopysupporting
confidence: 86%
See 1 more Smart Citation
“…[5] The hyperfine coupling constant evaluated from the line spacing (27 G) in Figure 2 is in good agreement with the literature value of 27.5 G. [29] This suggests that MCRs formed by intermolecular hydrogen abstraction also exhibit three-line EPR spectra. [28,30] The EPR spectrum observed at 27% conversion during the tBA polymerization at 60 8C is in agreement with the simulated spectrum as shown in Figure 3a and b: a a ¼ 18.1 G and a b ¼ 10.3 and 28.3 G for PRR (95%) and a b ¼ 28.0 G for MCR (5%). The small radical expelled from 1 was not detected.…”
Section: Observation Of Radicals By Epr Spectroscopysupporting
confidence: 86%
“…[28][29][30] Gilbert et al reported that MCRs formed by intramolecular hydrogen abstraction (backbiting) of the tetramer or higher oligomer radicals of acrylic acid exhibit three-line EPR spectra. [29] Photolysis of TBP in the presence of poly(tBA) in benzene was carried out at 60 8C and a broad three-line spectrum assignable to 2 was observed ( Figure 2).…”
Section: Observation Of Radicals By Epr Spectroscopymentioning
confidence: 99%
“…The main general ones are (1) the S-like shape of the kinetic curves, indicating the presence of autoacceleration and autodecelation processes; (2) a great posteffect, that is, being dark after UV illumination, stopping the postpolymerization process observed from the autoacceleration stage; and (3) a high (to 10 Ϫ1 mol/m 3 ) concentration of radicals discovered by EPR spectroscopy "in situ" until the end of the polymerization process. [1][2][3][4][5][6][7][8] Two main conceptions have been formulated with the aim of explanation of such peculiarities for the polymerization process to high conversion. The first is based upon the diffusion-controlled character of elementary reactions assigned to the classic kinetic scheme.…”
Section: Introductionmentioning
confidence: 99%
“…spectra. Whereas the EPR parameters of the radical for EGDM are available, 14 in case of styrene we calculated some EPR parameters of the initiator and propagator radicals for better identification and compared with the measured ones. As a model compound for the initiator radical in eq.…”
Section: Figurementioning
confidence: 99%